Outcomes of Pediatric Neurosurgical Cases Managed by General Neurosurgeons: A Retrospective Study from Eastern India - Acharya, Abhijit; Senapati, Satya Bhusan; Puppala, Sumirini; Mahapatra, AK (Indian Journal of Neurosurgery, 2023)
India is home to almost 19% of the world's children. The burden of diseases in the pediatric age group is quite high and is just the tip of the iceberg. In India, there are very few neurosurgeons who deal with cases in the pediatric age group. Most parents avoid surgical management for their child due lack of confidence in the expertise of the neurosurgeon in handling pediatric cases. Many challenges are encountered in the pediatric population during the pre-, intra- and post-operative period.The aim of this study is to study the demographic profile and respective outcomes of pediatric neurosurgical cases (below 18 years of age).A retrospective study of cases over a period of 1.5 years in the Department of Neurosurgery, Institute of Medical Sciences and Sum Hospital was done. The variables analyzed were age group, sex, diagnosis, elective or emergency, neurological examination, and outcome. Data analysis was done using Version 3.0.2; 2013-09-25 for Statistical Computing (IBM Corporation's SPSS programme, version 27.0, 2020). Literature review was done through the NCBI PubMed, Scopus, Embase, and Google Scholar databases. Quality of life was assessed by the disability-adjusted life years (DALY) score approved by the World Health Organization.The majority of the patients had significant improvement in achieving milestones with reduced morbidity and one case of mortality.To conclude, we have managed all cases of pediatric age group in a general neurosurgery department with utmost skill and meticulous surgery, with less than 0.1% mortality. In the cases that pertain to low resourced centers, areas, and countries where general neurosurgeons are mandated and obliged to perform pediatric neurosurgical procedures, we general neurosurgeons should take it as a challenge to manage these pediatric cases as our study showed appreciable results although the need for specialized pediatric neurosurgical care cannot be overemphasized.
Keywords: pediatric neurosurgery; neurological demography; children; tumors; neurosurgery